Local Agenda 21 and Culture: Lessons from the Czech Republic - Hájek, Oldřich; Novosák, Jiří; Bednář, Pavel (Culture and Local Governance / Culture et gouvernance locale, 2011)
Sustainable development represents one of the leading concepts of modern society. On the local level, sustainable development principles are implemented by Local Agenda 21 (LA 21), the most influential output of the 1992 Earth Summit. Although culture is not explicitly mentioned in its definitions of sustainable development, there are close links between culture, on one side, and the economic, social, and ecological dimensions of sustainable development, on the other. Culture is an important factor of social cohesion and economic development, and culturally led urban and rural regeneration projects may have also positive ecological impacts. Moreover, the efforts to maintain local culture may be the main impetus in accepting the LA 21 principles in culturally rich communities.This article assesses the importance of culture in the LA 21 implementation process, with two municipalities from the Czech Republic as case studies. Findings point to complex links between LA 21 and culture. Uherské Hradiště is a culturally rich city that is progressive in the LA 21 implementation process; however, our findings show that LA 21 and culture live independent lives in planning processes. Zděchov tells a completely different story of the relationship between culture and LA 21: here, local culture has become the leitmotif of the LA 21 implementation process. The goal to maintain and develop local culture has been the prime motivation behind the decision to accept the LA 21 principles. The case studies share several common characteristics. In both cases, LA 21 has stimulated public interest in both municipalities, and ever more local actors are getting involved in the LA 21 implementation process. A combination of top-down and bottom-up approaches has been applied in this process. LA 21 is also perceived as a good brand for project management, and may be an incentive for innovations in strategic planning.